Analisis Penggunaan Plasticizer (Gliserol dan Sorbitol) dalam Pembuatan Bioplastik dari Pati Bengkuang Menggunakan Pelarut CH3COOH 5% - Enda, Ludgardis Yustika; Fajarwati, Yuni Eka; Widyastuti, Fikka Kartika (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2023)
Using bioplastics as a substitute for plastics that decompose more slowly is one way to overcome the problem of plastic waste. Natural polymers are the basic ingredients of biodegradable plastics, or bioplastics. Water and microorganisms are two tools that can be used by the environment to break down bioplastics. The main qualitative research methods in this research are observation of test phenomena, biodegradation assessment, and water absorption capacity assessment. Biodegradation tests measure the rate at which microorganisms or the environment degrades biodegradable polymers. To find out how effectively plastic decomposes, samples of biodegradable plastic are planted in the soil. Based on samples with glycerol sorbitol content of 15%, 20% and 25%. The 15% concentration group experienced damage or weight loss more quickly compared to samples containing 20%, 25% and 15% glycerol. One thing that is taken into account in evaluating the quality of bioplastics is their ability to absorb water. Because it is related to how long plastic can last in storage, the greater the water absorption capacity of a bioplastic, the worse its quality. From the analysis of biodegradation and water absorption tests, the lower the concentration of glycerol and sorbitol, the more fragile the plastic produced, less elastic, and more easily decomposed by water, soil and other microorganisms. The higher the concentration of glycerol and sorbitol, the higher the results obtained. The plastic produced will be harder so that it is not easily decomposed or damaged.